2012
DOI: 10.1186/1687-1499-2012-337
|View full text |Cite
|
Sign up to set email alerts
|

Traffic steering by self-tuning controllers in enterprise LTE femtocells

Abstract: Femtocells have been suggested as a promising solution for the provision of indoor coverage and capacity. This article investigates the problem of re-distributing traffic demand between long-term evolution (LTE) femtocells with open access in an enterprise scenario. Several traffic sharing algorithms based on automatic tuning of femtocell parameters are considered. The proposed algorithms are implemented by fuzzy logic controllers. Performance assessment is carried out in a dynamic system-level simulator. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…The proposed MLB algorithm is compared with the non-optimized network (baseline) and the power traffic sharing (PTS) algorithm presented in reference [19] which tunes femtocell transmission power based on comparing the call blocking ratio of a cell to the average call blocking ratio of its neighboring cells. To quantify the advantages and disadvantages of the MLB algorithm, the indicators described in Section 3 are assessed: UDR and UHR.…”
Section: Performance Assessment Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed MLB algorithm is compared with the non-optimized network (baseline) and the power traffic sharing (PTS) algorithm presented in reference [19] which tunes femtocell transmission power based on comparing the call blocking ratio of a cell to the average call blocking ratio of its neighboring cells. To quantify the advantages and disadvantages of the MLB algorithm, the indicators described in Section 3 are assessed: UDR and UHR.…”
Section: Performance Assessment Methodologymentioning
confidence: 99%
“…The authors in [18], proposed a method to adjust hysteresis margins depending on an estimation of the distance from the base station to the user equipment (UE), reduces the number of redundant handovers (HOs) while keeping the throughput of femtocells as high as possible. The work shown in [19] studied the persistent congestion problems on traffic distribution in LTE femtocell enterprise scenario. That work implemented and compared several traffic sharing algorithms that tune femtocell transmission power and handover margins, following a fuzzy logic controller (FLC) scheme in order to automatically adjust femtocell parameters.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies on load sharing are focused on macrocellular scenarios in different radio access technologies (e.g., time division multiple access/frequency division multiple access -TDMA/FDMA [10], wideband code division multiple access -WCDMA [11], and orthogonal frequency division multiple access -OFDMA [12,13]). Recently, the analysis has been extended to heterogeneous office scenarios with open-access femtocells [14]. Results presented there showed that traffic sharing in OFDMA femtocell networks is a challenging task due to the full frequency reuse currently used by operators.…”
Section: Introductionmentioning
confidence: 99%